Case report: Safety of Tumor Treating Fields therapy with an implantable cardiac pacemaker in a patient with glioblastoma - Biedermann, Gregory B.; Merrifield, Kathleen; Lustgarten, Leonardo (Frontiers in Oncology, 2024)
Tumor Treating Fields (TTFields) therapy is an anti-cancer treatment modality that is delivered noninvasively to the tumor site via skin-placed arrays. The therapy is US Food and Drug Administration (FDA) approved and Conformité Européenne (CE) marked for adults with newly diagnosed and recurrent glioblastoma (GBM) (grade 4 glioma in the European Union). To date, there are limited data on the safety and efficacy of TTFields therapy in patients with implanted cardiac pacemakers. Herein, we report a case of a 79-year-old male patient with GBM receiving TTFields therapy with a prior medical history of cardiac events necessitating a cardiac pacemaker. The patient presented to the emergency department in May 2021 with newly onset left-sided weakness along with seizures. Based on an initial evaluation and results of the initial computed tomography (CT) scans (May 2021), the patient was clinically diagnosed with a high-grade glioma which was later confirmed as IDH wildtype following a biopsy. He was treated with radiotherapy (40 Gy in 15 fractions), followed by adjuvant temozolomide (TMZ) (75 mg/m 2 ). TTFields therapy was initiated alongside maintenance TMZ (150 mg/m 2 ). Average TTFields therapy usage was 67% throughout the duration of treatment. Follow-up CT scans (February and May of 2022) indicated stable disease. CT scans in August 2022 showed an increase in size of a mass with heterogeneous contrast enhancement and the patient subsequently passed away in October 2022. The patient's last cardiac tests demonstrated that the pacemaker was operational with adequate cardiac function. This report suggests that TTFields therapy concomitant with an implanted electronic device may be safe in patients with GBM.